The Hidden Heterogeneity of Inflation and Interest Rate Expectations: The Role of Preferences - Lena Dräger; Michael J. Lamla; Damjan Pfajfar (Center for Economic Studies and ifo Institute (CESifo), 2022)
Using a new consumer survey dataset, we show that macroeconomic preferences affect expectations and economic decisions through different channels. While household expectations are on average inversely related to preferences, households with the same inflation or interest rate expectations can differently assess whether the level of the corresponding variable is appropriate or too high/too low. This `hidden heterogeneity' in expectations is correlated with sociodemographic characteristics and affects durable spending and saving decisions. We also show that the variation in inflation preferences can be explained with risk preferences. Overall, this adds a new dimension to the definition of anchored expectations.
Keywords: E31; E52; E58; D84; 330; macroeconomic expectations; monetary policy perceptions; inflation and interest rate preferences; risk preferences; survey microdata